Depression Symptoms on The Dialogues of Laney Brooks in I Smile Back Movie - Dicky Perdana; I Wayan Juniartha (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2023)
This qualitative research aims to find out and analyze depression symptoms of Laney Brooks on dialog I Smile Back movie. This research focus on analyzing one of four type bipolar disease episodes it called depression on the main character named Laney Brooks. The research methods used in this research are descriptive qualitative methods and library research methods and also observation method was used to get the data for this study by watching I Smile Back Movie and also using a note-taking technique to identify, and classify the data contains depression symptoms of Laney Brooks on dialog. NAMI (National Alliance Mental Illness) and Analyze Fiction by Kenney, W. P. (1966) theory has been applied in this research. The final result shows that Laney Brooks' depression symptoms are indicated by symptoms such as changes in appetite or weight, concentration and memory problems, irritability, and feelings of worthless or guilt. The symptoms of depression are shown by Laney through her dialogue. Keywords: Bipolar disorder, Depression, Dialogue, Movie.